Sectoral Decomposition of Changes in Pakistan’s Poverty: The New Interface. - Zaman, Khalid; Khilji, Bashir Ahmad (Journal of Poverty)
Propoor economic and regional policies focus on increasing the economic returns to the productive factors that the poor possesses. The objective of the study is to examine the impact of intrasectoral gains/losses and intersectoral shifts in population on aggregate changes in poverty in Pakistan. The result shows that the urban and rural sectors contributed to the increase in aggregate poverty, though the “interaction effect” and the “population shift effect” alleviated poverty, the overall impact was negligible.